1982
DOI: 10.1080/00039896.1982.10667569
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Lead Storage in Teeth and Bones: An Epidemiologic Approach

Abstract: Lead content in teeth of three Belgian populations with different exposures are considered in the framework of a three-compartment model describing lead exchanges in the body. The value of the first-order kinetic constant governing the transfer of lead from blood to teeth is shown to be approximately 1.85 yr-1, which is in good agreement with other studies using stable isotope tracers on a few subjects. Application of these findings to bones, where, contrary to teeth, remobilization processes cannot be neglect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
0
1

Year Published

1991
1991
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 23 publications
0
30
0
1
Order By: Relevance
“…Many studies have demonstrated that bone lead levels remain elevated despite declines in blood lead, raising the issue of whether bone lead may be a better biological marker for predicting chronic toxicity (3,4). Recent studies suggest that significant amounts of lead are released from bone.…”
mentioning
confidence: 99%
“…Many studies have demonstrated that bone lead levels remain elevated despite declines in blood lead, raising the issue of whether bone lead may be a better biological marker for predicting chronic toxicity (3,4). Recent studies suggest that significant amounts of lead are released from bone.…”
mentioning
confidence: 99%
“…Epidemiological studies have shown that the skeleton contains most of the lead body burden in humans (about 90% in adults and 70% in children). 17 The more polluted the environment, the higher the lead level in teeth. Thus, differences in the lead level were found between urban or industrial areas and rural zones or between different areas of the same city.…”
Section: Discussionmentioning
confidence: 99%
“…As a consequence, the lead levels are significantly increased in the blood and body organs of human. 16 It accumulates mainly in calcified tissues in the body, 17 but the central nervous system is considered to be the critical organ of lead toxicity in children. 18 From data published in the literature, lead is one of the elements accumulated mainly in calcified tissues, such as teeth and bones.…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of lead in dentin of permanent teeth may continue for the life of the tooth (Steenhout 1982;Steenhout and Pourtois 1981). Because it is in direct contact with the external environment, enamel lead levels may be more influenced than dentin lead by external lead levels and tooth wear (Purchase and Fergusson 1986).…”
Section: Bone and Tooth Lead Measurements The Development Of Noninvamentioning
confidence: 99%